1993
DOI: 10.1007/bf00685839
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofO 6-benzylguanine on the response to 1,3-bis(2-chloroethyl)-1-nitrosourea in the Dunning R3327G model of prostatic cancer

Abstract: The DNA-repair protein O6-alkylguanine-DNA alkyltransferase is known to protect tumor cells from the antitumor effects of carmustine (BCNU). This repair protein was inactivated in Copenhagen rat prostate tumors by treatment with O6-benzylguanine in attempts to increase the effectiveness of BCNU therapy. The alkyltransferase activity in the liver, kidney, lung, and prostate of Copenhagen rats was 66, 37, 65, and 122 fmol/mg protein, respectively. The activity in the Dunning R3327G rat prostate tumor was found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…31 At micromolar concentrations, O 6 BG depletes Ն 99% of AGT activity within minutes in tumor cell lines in vitro and in human tumor xenografts in vivo, 30 and AGT remains depleted for 8 hours to more than 24 hours after a single dose of O 6 BG. [33][34][35] In adults with brain tumors, the dose of O 6 BG required to deplete AGT in tumor tissue that had been resected 6 hours to 25 hours after a single intravenous dose of O 6 BG, was determined to be 100 to 120 mg/m 2 . [33][34][35] In adults with brain tumors, the dose of O 6 BG required to deplete AGT in tumor tissue that had been resected 6 hours to 25 hours after a single intravenous dose of O 6 BG, was determined to be 100 to 120 mg/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…31 At micromolar concentrations, O 6 BG depletes Ն 99% of AGT activity within minutes in tumor cell lines in vitro and in human tumor xenografts in vivo, 30 and AGT remains depleted for 8 hours to more than 24 hours after a single dose of O 6 BG. [33][34][35] In adults with brain tumors, the dose of O 6 BG required to deplete AGT in tumor tissue that had been resected 6 hours to 25 hours after a single intravenous dose of O 6 BG, was determined to be 100 to 120 mg/m 2 . [33][34][35] In adults with brain tumors, the dose of O 6 BG required to deplete AGT in tumor tissue that had been resected 6 hours to 25 hours after a single intravenous dose of O 6 BG, was determined to be 100 to 120 mg/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…First, O 6 -benzylguanine (BG) was described as a potent inactivator of the AGT capable of enhancing the antitumor efficacy of BCNU in cell lines and in human tumor xenografts (14,(22)(23)(24)(25). Since many tumors express high levels of AGT and are resistant to BCNU and related compounds, BG represents a significant advance in the approach to biochemical modulation of tumor drug resistance (25). Not surprisingly, in preclinical toxicology, myelosuppression was dose limiting with BG and BCNU (26).…”
mentioning
confidence: 99%
“…Indeed, downmodulation of ATase levels via the use of O 6 -beG can be used as a means of sensitizing otherwise resistant tumors to killing by O 6 -alkylating agents. 21,[23][24][25]47 However, the effects of O 6 -beG are not restricted to tumor tissue, and the use of this inactivator before treatment with O 6 -alkylating agents also results in toxicity to normal cells, including those of the hemopoietic system. 20,26 -28 Thus, a strategy has emerged whereby it may prove possible to enhance the therapeutic effects of the O 6 -alkylating agents; this strategy incorporates the use of potentially powerful tumor sensitizers such as O 6 -beG.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, the use of analogs of O 6 -alkG, such as O 6 -benzylguanine (O 6 -beG), has been demonstrated to lead to tumor sensitization if used in combination with O 6 -alkylating agent therapy. [21][22][23][24][25] However, a major impediment of this strategy may be the lack of tumor specificity of O 6 -beG, because a number of studies have shown that this approach also leads to increased killing of normal tissues. 20,26 -28 The discovery and development of various mutant forms of ATase that exhibit different levels of resistance to inactivation by O 6 -beG 29,30 has led to the possibility of developing a gene therapy strategy in which tumor sensitization might be combined with normal tissue protection to increase the therapeutic index.…”
mentioning
confidence: 99%